Maternal and perinatal outcome in eclampsia and factors affecting the outcome: a study in North Indian population - Pannu, Deepika; Das, Banashree; Hazari, Paramita; Shilpa, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Worldwide eclampsia is a leading cause of maternal and perinatal mortality and morbidity. Hence the importance of continued efforts in reviewing each women with eclampsia and to analyze factors affecting the outcome. Aims of the study were to evaluate maternal and fetal outcome in patients of eclampsia and factors affecting the outcome. Methods: A retrospective epidemiological study was undertaken in the department of obstetrics and gynaecology, VMMC & Safdarjung hospital, New Delhi during the period ‘January to December 2010’. Women who presented as eclampsia or developed eclampsia during hospital stay were included in the study. Data analysed included various maternal parameters and fetal parameters and the outcome of the pregnancy. Pearson Chi-square test was used to see association between two parameters. Results: During the defined period incidence of Eclampsia was 3.2 per 1000 deliveries. Maternal death occurred in 8.4% of patients and still birth in 18.8%. Inadequate & delayed initiation of treatment and preterm deliveries was found to be associated with poor maternal and fetal outcome. As the time interval between ‘onset of fit and delivery’ increased, chances of adverse outcome also increased. However, age, parity, onset of seizures before, during or after delivery was not found to have any effect on maternal and fetal outcome. Conclusions: It can be concluded that better antenatal care, early recognition of disease, timely referral, early initiation of treatment and termination of eclamptic patients improves outcome. Management of eclamptic patients should be performed at tertiary care centres, where ICU facilities, NICU facilities and multidisciplinary units are available.